2004
DOI: 10.1016/j.newast.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Searching for radiative pumping lines of OH masers: II. The 53.3 ?m absorption line towards 1612 MHz OH maser sources*1

Abstract: This is the second paper in a series aiming at searching for infrared pumping lines for galactic 1612 MHz OH masers. Our paper I is devoted to the 34.6 µm absorption lines in ISO SWS spectra towards a large sample of galactic OH/IR sources. This paper analyzes the 53.3 µm line in the ISO LWS spectra towards a similar sample of OH/IR sources. A search with position radius of 1 arcmin in ISO Data Archive (IDA) results in 137 LWS spectra covering 53.3 µm associated with 47 galactic OH/IR sources and 4 ones associ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…From the ISO data and the non detection of these IR lines in neither of our two sources (Vy 2-2 or K 3-35, see He & Chen 2004;He et al 2005), we deduce that the line to continuum ratio is, from their 3 sigma upper limits, smaller than 0.15 and 0.19 for K 3-35 and Vy 2-2, respectively. The exact pumping efficiency is unknown but even if it would reach 25% as required by most theoretical models (see for example Elitzur et al 1976;Thai-Q-Tung et al 1998) or even by the model by Gray et al (2005) who proposed an alternative route mainly using the 53 μm photons to explain the 1612 MHz line in late type stars, we do not expect that IR pumping is playing a dominant role 7 .…”
Section: Remarks On Oh Pumpingmentioning
confidence: 56%
“…From the ISO data and the non detection of these IR lines in neither of our two sources (Vy 2-2 or K 3-35, see He & Chen 2004;He et al 2005), we deduce that the line to continuum ratio is, from their 3 sigma upper limits, smaller than 0.15 and 0.19 for K 3-35 and Vy 2-2, respectively. The exact pumping efficiency is unknown but even if it would reach 25% as required by most theoretical models (see for example Elitzur et al 1976;Thai-Q-Tung et al 1998) or even by the model by Gray et al (2005) who proposed an alternative route mainly using the 53 μm photons to explain the 1612 MHz line in late type stars, we do not expect that IR pumping is playing a dominant role 7 .…”
Section: Remarks On Oh Pumpingmentioning
confidence: 56%
“…ISO observations of the IRC+10420 supergiant directly confirmed that the 34.6 µm photons are involved in the 1612 MHz line pumping (Sylvester et al 1997). In OH/IR and Miras the 1612 MHz maser is probably pumped by the alternative route, beginning with the 53.3 µm photons (He & Chen 2004). Therefore, if the radiative pumping is dominant in OH17.7−2.0, our observations imply that only a local rise of the infrared flux may correspond to the burst of the two 1612 MHz features.…”
Section: Discussionmentioning
confidence: 91%
“…There are only a few OHMs in which the important 53 μm transition has been measured (e.g., He & Chen 2004); this could be potentially observed in larger numbers of galaxies with SOFIA. The Herschel observatory can also supplement the IRS by measuring the 79 and 119 μm OH transitions in large samples of ULIRGs (e.g., Fischer et al 2010).…”
Section: Predictions and Future Observationsmentioning
confidence: 99%